INDIAN FOLK AND TRIBAL ART: A STUDY - Patel, Varsha (International Journal of Research -GRANTHAALAYAH, 2026)
Tribal and folk arts of India represent the ancient, rich, and vibrant traditions of Indian cultural heritage. These arts are not merely aesthetic expressions; they are deeply connected to nature worship, religious beliefs, social structures, community life, and oral traditions. Evolving from prehistoric times, tribal and folk art has provided a visual form to the cultural consciousness of Indian society. This research paper examines the major tribal and folk art styles of India—such as Warli, Gond, Pithora, Saura, Adivasi, Santhal, Chitradaan, Pattachitra, Thangka, Madhubani, Mandana, Phad, Kalighat, Patua, Kalamkari, and Cheriyal—through sociological, cultural, and religious perspectives. Through these arts, the study explores the religious beliefs, rituals, collective memory, women-centered expressions, and environmental awareness of tribal and folk communities. In conclusion, tribal and folk arts are not only the cultural memory of India’s past but also a source of social unity, cultural identity, and creative consciousness for contemporary society. Their preservation, promotion, and academic study have become increasingly relevant in the present context.